2015
DOI: 10.1891/1933-3196.9.4.174
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and Physiological Outcomes Pre- and Post-EMDR Therapy for a Woman With PTSD: A Case Study

Abstract: This article provides a comprehensive review of the literature on the neurocognitive impact of posttraumatic stress disorder (PTSD) and reports on a quantitative single-case study, which investigated whether eye movement desensitization and reprocessing (EMDR) therapy would change the neuropsychological and physiological responses of an 18-year-old female client diagnosed with comorbid PTSD and major depressive disorder. Eleven 90-minute weekly sessions of EMDR therapy were provided. We used biofeedback equipm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…However, the group of women who received EMDR therapy and who were exposed to physical, psychological or sexual violence showed greater reductions in levels of anxiety, depression and posttraumatic symptoms in the posttreatment evaluation. The results indicate a relationship between interventions focused on populations of women victims of violence from diverse sociocultural contexts and improvement after undergoing treatment based on EMDR (35,37).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the group of women who received EMDR therapy and who were exposed to physical, psychological or sexual violence showed greater reductions in levels of anxiety, depression and posttraumatic symptoms in the posttreatment evaluation. The results indicate a relationship between interventions focused on populations of women victims of violence from diverse sociocultural contexts and improvement after undergoing treatment based on EMDR (35,37).…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies have reported the benefits of EMDR in the physical and mental health of women victims of violence (35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously assessing the qualitative impact of EMDR on participants, alongside quantitative data collection, addressed the recommendation identified by Marich et al (2020), that qualitative assessments should not primarily follow or come after quantitative ones, as most existing ones had. In terms of clients' personal experiences of EMDR, qualitative findings of this study echo prior findings that EMDR treatment decreases vividness of traumatic memories (Cotter et al, 2017), increases insight about the past (Shipley et al, 2021), strengthens self-confidence (Cotter et al, 2017), increases positive emotions (Cotter et al, 2017), drives transformative change (Shipley et al, 2021), and improves cognitive functioning (Aranda et al, 2015;Camacho-Conde, 2020). Transformative change and improved cognitive functioning are expected changes related to the AIP model, which addresses treatment at the source of pathology, targeting insufficiently processed information from a disturbing event early in life (Shapiro, 2018).…”
Section: Discussionsupporting
confidence: 75%
“…Uniquely, EMDR participants experienced distressing memories less clearly and vividly, and CBT participants experienced adoption of emotional regulation tools (Cotter et al, 2017). Multiple additional case studies demonstrate EMDR improving cognitive functioning, particularly related to participant's attention profile (Camacho-Conde, 2020;Aranda et al, 2015). In reviewing existing qualitative research, Marich et al (2020) identified that a number of qualitative assessments specifically followed quantitative ones, reflecting a more quantitative orientation in EMDR research.…”
Section: Emdr As a Treatment Optionmentioning
confidence: 99%
“…Efficacy in the child and adolescent population is studied in 8 of them (Ahmad et al, 2007;Chemtob et al, 2002;de Roos et al, 2011;Diehle et al, 2015;Jaberghaderi et al, 2004;Kemp et al al., 2010;Scheck et al, 1998;Soberman et al, 2002). In addition, there is evidence of its usefulness for the treatment of people with impaired executive functions and altered attentional processes after trauma (Camacho-Conde, 2020;Estrada, et al, 2015).…”
Section: Trauma Treatment: Emdr Therapymentioning
confidence: 99%